2011
DOI: 10.1108/14635771111180725
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain management practices in the electronics industry in Malaysia

Abstract: PurposeThe purpose of this paper is to explore the effects of different dimensions of supply chain management practices (SCMP) on supply chain performance (SCP) in the electronics industry in Malaysia.Design/methodology/approachThe study employed the quantitative method where convenience sampling and self‐administrated survey questionnaires were sent to 125 electronics firms in Malaysia. The research framework was tested using variance‐based structural equation model, the partial least squares (PLS) method.Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(60 citation statements)
references
References 97 publications
(133 reference statements)
5
44
0
6
Order By: Relevance
“…The moderating effect of competitive intensity on the relationship between postponement and SC effectiveness was negative, but insignificant. Our results were consistent with the results of Li et al (2004) and Sundram et al (2011) who found that postponement affected competitive advantage and SC performance respectively. …”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…The moderating effect of competitive intensity on the relationship between postponement and SC effectiveness was negative, but insignificant. Our results were consistent with the results of Li et al (2004) and Sundram et al (2011) who found that postponement affected competitive advantage and SC performance respectively. …”
Section: Resultssupporting
confidence: 83%
“…That means the higher customer integration efforts undertaken when competitive intensity exists, the lower SC efficiency levels are yielded. Generally, our results were consistent with the results of Sundram et al (2011) and Lee et al (2007) who found that customer integration did not affect SC performance and cost performance respectively. The possible explanation is that customer integration efforts require additional investments and resources to enable a timely and reliable contact with customers.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…In addition, information sharing among supply chain members contributes to risk-sharing, especially during a stage of transferring the information (Kocoglu, et al 2011). Information sharing has been previously proven to have a significant and positive relationship with business performance (Moberg, Cutler, Gross, & Speh, 2002;Fawcett, Osterhaus, Magnan, Brau, & McCarter, 2007;Sanders, Autry, & Gligor, 2011;Sundram, Ibrahim, & Govindaraju, 2011). Sanders et al (2011) expect that the ultimate cause of achieving good firms' performance is by sharing truthful information at a strategic and operational level.…”
Section: (A) Information Sharingmentioning
confidence: 99%